What Is Caring in Nursing?: Sorting Out Humanistic and Christian Perspectives. Issue 3 (July 2018) - Newbanks, R. Shirlene; Rieg, Linda S.; Schaefer, Beverly
Abstract : ABSTRACT: Historically, some propose that organized nursing was founded on biblical principles and the caring behaviors and characteristics of Christ, and that caring originates with God. More recently, perceptions of caring have shifted to a humanistic, postmodern worldview, where the source of caring is within the person. This integrative literature review synthesized caring literature from humanistic, postmodern, and biblical, theological worldviews. Findings reveal that 95% of research and 85% of nonresearch publications were written from the humanistic perspective. The results lay a foundation for an alternative middle range theory on caring from a biblical worldview for nurses holding Christian beliefs.